(untitled) (Al-Muwazanah: Indonesian Journal of Islamic Economics, 2025)
This study aims to examine the influence of E-commerce and Accounting Information Systems on entrepreneurial decision-making among Accounting students. The research employs a quantitative approach with an associative design. Data were collected through the distribution of questionnaires using a survey method to 50 respondents. The findings reveal that both E-commerce and Accounting Information System variables have a positive and significant effect on entrepreneurial decision-making. These results support the Technology Acceptance Model (TAM), which posits that the acceptance and utilization of technology can enhance individuals’ behavioral intentions, including decisions to engage in entrepreneurship. Based on these findings, it can be concluded that proficiency in E-commerce and a solid understanding of accounting information systems are important factors that encourage students to pursue entrepreneurial ventures in today’s digital era